Risk factors for cardiovascular disease in people with idiopathic pulmonary fibrosis: a population-based study - Dallywater, William; Powell, Helen A.; Hubbard, Richard B.; Navaratnam, Vidya (Elsevier, 2015)
OBJECTIVE: People with idiopathic pulmonary fibrosis (IPF) have been shown to be at an increased risk for cardiovascular (CV) disease, but reasons for this are unknown. The aim of this study was to compare the prevalence of common CV risk factors in people with IPF and the general population and establish the incidence of ischemic heart disease (IHD) and stroke after the diagnosis of IPF, controlling for these risk factors.